Hypocholesterolemic effects of a polysaccharide isolated from Balangu (Lallemantia royleana) seeds in Wistar rat fed on a cholesterol-containing diet: Effects of a polysaccharide isolated from Balangu - Mohammed Abdulameer Farhan; Amal Feki; Intissar Kammoun; Malek Aroui; Manel Naifar; Rim Kallel; Fatma Makni Ayadi; Tahia Boudawara; Choumous Kallel; Adil Abaed Hassoni; Ben Amara, Ibtissem (Cellular and Molecular Biology, 2022)
The present study aimed to evaluate the antioxidant effects of polysaccharide (PS) isolated from Balangu Shirazi (Lallemantia royleana) seeds in vitro as well as on the hypercholesterolemic diet-induced liver and kidney injury in adult rats. PS was structurally characterized by Fourier-transformed infrared, which confirmed the presence of bands characteristic of polysaccharides. Functional properties of PS were investigated based on water solubility index, holding and emulsifying capacities. The antioxidant activities were confirmed by DPPH radical scavenging assays, reducing power and the chelating effect assay. The administration of PS to a hypercholesterolemic diet for 30 days in Wistar rats significantly improved the liver and kidney levels in malondialdehyde, advanced oxidation protein products, glutathione, superoxide dismutase, glutathione peroxidase and in vitamin C. The oxidative stress profile was confirmed by hematological and plasma biochemical parameters. In addition, histological alterations were significantly ameliorated in liver and kidney tissues. The study strengthens the hypothesis that the herbal polysaccharide can be used as a novel antioxidant and hypocholesterolemic compound against hyperlipidemia-induced atherosclerosis.